2020
DOI: 10.1007/s40620-020-00790-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal function on admission in COVID-19 patients: an analysis of the international HOPE COVID-19 (Health Outcome Predictive Evaluation for COVID 19) Registry

Abstract: Background Coronavirus disease 2019 (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Despite its international aggressive extension, with a significant morbidity and mortality, the impact of renal function on its prognosis is uncertain. Methods Analysis from the international HOPE-Registry (NCT04334291). The objective was to evaluate the association between kidney failure severity on admission with the mortality of patients with SARS-CoV-2 infection. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
112
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 22 publications
9
112
1
2
Order By: Relevance
“…While the study by Williamson et al [13] provides important information on the epidemiology of COVID-19 and is the first to convincingly demonstrate the importance of CKD as a risk factor for COVID-19 mortality, to our knowledge, this is the first study analyzing the combined effect of CKD and AKI in COVID-19 hospitalized patients in whom preexisting CKD has been specifically investigated on the basis of kidney function (eGFR and urinalysis) within the 180 days before COVID-19 diagnosis. Even when we estimated the prevalence of CKD based on the reported medical history, we observed a significantly higher prevalence of CKD (11.8%) as compared to that described in early reports in China (0.7%) [14] and in Europe (8.5%) [15] on a historical basis. This difference might be explained by the older age of our population and the high prevalence of multiple comorbidities, both well-established risk factors for chronic renal disease [16].…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…While the study by Williamson et al [13] provides important information on the epidemiology of COVID-19 and is the first to convincingly demonstrate the importance of CKD as a risk factor for COVID-19 mortality, to our knowledge, this is the first study analyzing the combined effect of CKD and AKI in COVID-19 hospitalized patients in whom preexisting CKD has been specifically investigated on the basis of kidney function (eGFR and urinalysis) within the 180 days before COVID-19 diagnosis. Even when we estimated the prevalence of CKD based on the reported medical history, we observed a significantly higher prevalence of CKD (11.8%) as compared to that described in early reports in China (0.7%) [14] and in Europe (8.5%) [15] on a historical basis. This difference might be explained by the older age of our population and the high prevalence of multiple comorbidities, both well-established risk factors for chronic renal disease [16].…”
Section: Discussioncontrasting
confidence: 73%
“…With regard to the incidence of AKI among COVID-19 patients, it has been reported with great heterogeneity, mainly because of variable definition criteria and different baseline populations considered [15,17]. In early reports, AKI was described as a rare event [14], while in larger cohorts of patients from China and the U.S., its incidence varied from 5 to 36% [3,4,18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observation in this study was in support of the studies by Guan et al in 2020 which showed that presence of comorbidities such as hypertension, obesity, chronic lung disease, diabetes, and cardiovascular disease adversely affect and directly correlates with poor clinical outcome of patients with COVID-19 [25,26]. Similarly, this study was also analogous to other studies by Oyelade et al and Uribarri et al in 2020 which show that renal failure in patients with COVID-19 is associated with increase in severity and in-patient mortality [27,28].…”
Section: Discussionsupporting
confidence: 82%
“…population, and renal failure may lead to more complications and higher in-hospital mortality. 24 Ischemic heart disease appeared equally prevalent in inpatients with COVID-19…”
Section: Sensitivity Analysismentioning
confidence: 99%